1997
DOI: 10.1046/j.1365-2249.1997.d01-1015.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of IL-13 mRNA, but not IL-4 mRNA, are found in vivo in peripheral blood mononuclear cells (PBMC) of patients with atopic dermatitis (AD)

Abstract: SUMMARYPrevious studies using in vitro systems with various stimuli have shown that PBMC from patients with AD show increased levels of IL-4 but decreased levels of interferon-gamma (IFN-g) compared with PBMC from normal controls. However, in vitro conditions do not always mimic the in vivo condition. We therefore believe that it is important to quantify the expression of these cytokines in freshly isolated PBMC. This study examines the expression of IFN-g, IL-4 and IL-13 mRNA in freshly isolated PBMC from adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 22 publications
7
41
0
Order By: Relevance
“…This selection was chosen in order to focus on typical allergic diseases, which are associated with high IgE production, which in turn is associated with high IL-4 expression by T cells. For AD, IL-13 expression was used as the entry criterion, as it is meant to play an important role in AD [30, 31]. Of note, IFN-γ was also detectable, but not different compared to healthy donors.…”
Section: Resultsmentioning
confidence: 99%
“…This selection was chosen in order to focus on typical allergic diseases, which are associated with high IgE production, which in turn is associated with high IL-4 expression by T cells. For AD, IL-13 expression was used as the entry criterion, as it is meant to play an important role in AD [30, 31]. Of note, IFN-γ was also detectable, but not different compared to healthy donors.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests an intrinsic predisposition of neonatal CD8+ T cells to secrete high levels of IL-13, consistent with the observed Th2 bias of the neonatal immune system. In studies using RT-PCR, IL-13 has been shown to be increased in PBMC of adult AEDS patients compared with healthy controls [20], and in investigations utilizing intracellular cytokine staining and flow cytometry, an increase in the frequency of both CD4+ and CD8+ T cells expressing increased levels of IL-13 in adult patients was demonstrated [21]. Moreover, a recent study in adults has demonstrated increased IL-13 in PBMC from adult AEDS patients in response to anti-CD3/CD28 stimulation [22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-13 and IL-4 can be produced by different cells (39) and are differentially regulated by mediators such as IFN-α (40). The exaggerated production of IL-13 is well documented in atopic and nonatopic asthma (41)(42)(43), atopic dermatitis (44,45), allergic rhinitis (46), and chronic sinusitis (47). IL-13 also plays an important role in the pathogenesis of type II granulomatous responses (48).…”
Section: Introductionmentioning
confidence: 99%